Adsorption of Brilliant Green onto Luffa Cylindrical Sponge: Equilibrium, Kinetics, and Thermodynamic Studies. (4th March 2014) - Segun Esan, Olaseni; Nurudeen Abiola, Oladoja; Owoyomi, Olanrewaju; Olumuyiwa Aboluwoye, Christopher; Olubunmi Osundiya, Medinat
Abstract : The sponge of Luffa cylindrical (LFC), a fibrous material, was employed as adsorbent for the removal of Brilliant Green (BGD) from aqueous effluent via batch studies. The optimum removal of BGD was found at pH 8.2 and the equilibrium was attained within 3 hours. The kinetic data are analyzed using several models including pseudo-first-order, pseudo-second-order, power function, simple elovich, intraparticle diffusion, and liquid film diffusion. The fitting of the different kinetics models to the experimental data, tested by error analysis, using the linear correlation coefficient r 2 and chi-square analysis χ 2, showed that the mechanism of adsorption process was better described by pseudo-second-order and power function kinetic models. The equilibrium isotherm data were analyzed using Langmuir, Freundlich, and Temkin models and the sorption process was described by the Langmuir isotherm with maximum monolayer adsorption capacity of 18.2 mg/g at 303 K. The thermodynamic properties Δ G 0, Δ H 0, and Δ S 0 showed that adsorption of BGD onto LFC was spontaneous, endothermic, and feasible within the temperature range of 303–313 K.